Modeling of axisymmetric wave modes in a poroelastic cylinder using spectral method - Karpfinger, Florian; Gurevich, Boris; Bakulin, Andrey (Acoustical Society of America, 2008)
Algorithm and code are presented which solve the dispersionequation for cylindrical poroelastic structures. The algorithm is based on thespectral method, which discretizes the underlying wave equations with thehelp of spectral differentiation matrices and solves the corresponding equationsas a generalized eigenvalue problem. The results are illustrated for thecase of a fluid-saturated free cylinder with open- and closed-pore boundaryconditions on its surface. The computed dispersion curves are in good agreementwith analytical results, which confirms the accuracy of the method.